Identity, society and transformative social categories dynamics of construction, configuration and contestation - Debal Kumar SinghaRoy (Thousand Oaks, California : Sage Publications India Pvt Ltd, 2018)
A comprehensive exploration on the concepts of identity and transformative social categories$1 (Bcaste, class, ethnicity, nationality and citizenship.s
Keywords: Identity (Psychology); Social groups